The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/21582440221102429
|View full text |Cite
|
Sign up to set email alerts
|

Underscoring the Relationship Between Education for Women and National Development in Nigeria

Abstract: This study assessed the impact of education for women at all levels (primary, secondary, and tertiary) on economic development and child welfare in Nigeria. The choice of these two domains was to give a thorough assessment economic impact of women’s education. The Augmented Dickey-Fuller (ADF) was used to test for the stationarity of variables. The Autoregressive Distributed Lag (ARDL) bound test with the aid of data obtained from World Bank indicators was employed for the analysis. The analysis revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Some husbands would have sponsored their spouses, but needed more funds to do so. Sharma (2010) and Obiageli et al (2022) complement this view that poverty is the major factor limiting women's education. Semela (2007) identified factors that explain females' higher academic dismissal rates than males.…”
Section: Qualification and Financial Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Some husbands would have sponsored their spouses, but needed more funds to do so. Sharma (2010) and Obiageli et al (2022) complement this view that poverty is the major factor limiting women's education. Semela (2007) identified factors that explain females' higher academic dismissal rates than males.…”
Section: Qualification and Financial Factorsmentioning
confidence: 97%
“…Even though girls and women were denied access to education in the past for various reasons, today, both men and women in Nigeria enjoy equal access to education -as long as obstacles, problems and peculiar difficulties do not arise on the way (Etejere, 2008). Obiageli et al (2022) found that women with secondary and tertiary education are more likely to contribute to Nigeria's economic growth and child welfare. Therefore, it was recommended that the government implement appropriate policies to increase women's education.…”
Section: Introductionmentioning
confidence: 99%
“…In Asia and developing countries, investments in women's education significantly impact faster economic growth (Altuzarra et al, 2021;Hassan & Cooray, 2015) and children's welfare (Aimua, 2021;Obiageli et al, 2022). Based on Laily's statement, the women contribution is not only limited to reproduction aspects, the growth and education of children will depend heavily on women.…”
Section: Higher Education For Girls Faster Growth For Allmentioning
confidence: 99%